Tissue-specific roles of regulatory T cells: mechanisms of suppression and beyond along with emerging therapeutic insights in autoimmune indications - Jugder, Bat-Erdene; Park, Eunchong; Du, Lijuan; Jawale, Chetan; Popov, Nikolay; Guo, Zengli; Bednar, Kyle J.; Ort, Tatiana (Frontiers in Immunology, 2025)
Regulatory T cells (Tregs) are central to immune homeostasis and controlling inflammation through multiple mechanisms, however, recent discoveries and advances in technology reveal that Tregs exert a diverse array of functions beyond mere immunosuppression, adapting uniquely to the specialized environments of tissues. This review delves into the multifaceted, tissue-specific mechanisms of Tregs, highlighting their roles in tissue repair, inflammatory modulation, and tolerance maintenance. We explore the developmental, functional, and metabolic pathways that drive Treg specialization across distinct organs, such as the central nervous system, gastrointestinal tract, joints, skin, and lungs, and examine how these insights advance the design of novel, targeted therapies for autoimmune and inflammatory disorders. This review will emphasize non-suppressive functions, discussing how Tregs can be harnessed in therapeutic applications tailored to specific tissue microenvironments, offering a promising new direction for the treatment of autoimmune diseases.